Role of Toll-Like Receptors in Neuroimmune Diseases: Therapeutic Targets and Problems - Li, Haixia; Liu, Shan; Han, Jinming; Li, Shengxian; Gao, Xiaoyan; Wang, Meng; Zhu, Jie; Jin, Tao (Frontiers in Immunology, 2021)
Toll-like receptors (TLRs) are a class of proteins playing a key role in innate and adaptive immune responses. TLRs are involved in the development and progression of neuroimmune diseases via initiating inflammatory responses. Thus, targeting TLRs signaling pathway may be considered as a potential therapy for neuroimmune diseases. However, the role of TLRs is elusive and complex in neuroimmune diseases. In addition to the inadequate immune response of TLRs inhibitors in the experiments, the recent studies also demonstrated that partial activation of TLRs is conducive to the production of anti-inflammatory factors and nervous system repair. Exploring the mechanism of TLRs in neuroimmune diseases and combining with developing the emerging drug may conquer neuroimmune diseases in the future. Herein, we provide an overview of the role of TLRs in several neuroimmune diseases, including multiple sclerosis, neuromyelitis optica spectrum disorder, Guillain-Barré syndrome and myasthenia gravis. Emerging difficulties and potential solutions in clinical application of TLRs inhibitors will also be discussed.